Tingkat Pendapatan dan Kesejahteraan Rumah Tangga Petani Jahe di Desa Taro, Kecamatan Tegallalang, Kabupaten Gianyar Pada Saat Pandemi Covid-19 - SUSILAWATI, NI KOMANG SRI; USTRIYANA, I NYOMAN GEDE; SUDARMA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023, 2023)
Income Level and Household Welfare of Ginger Farmers in Taro Village, Tegallalang District, Gianyar Regency During the Covid-19 Pandemic Ginger ( Zingiber officinale ) contains antioxidants that are good for maintaining body resistance during a pandemic. The government's response to reduce the spread of Covid-19 resulted in lowering economic performance. The purpose of the study was to determine the level of income, the level of family welfare of ginger farmers and the constraints on ginger cultivation in Taro Village, Tegallalang District, Gianyar Regency during the Covid-19 pandemic. The analytical method used is quantitative and qualitative with research variables namely farm income, household income ( on farm , off farm and non farm ), welfare level with indicators according to BPS 2020 and cultivation constraints by direct interviews. The results showed that ginger farming income during the pandemic was Rp. 114,073,361.00 per hectare per growing season. The contribution of ginger farmers' household income from on-farm income is 13.40 percent, off-farm income is 13.23 percent and non-farm income is 73.37 percent. The welfare level of ginger farming families, 82.93 percent is classified as prosperous and 17.07 percent is classified as not prosperous. The cultivation constraints experienced by ginger farmers are 36.59 saying they are experiencing extreme weather changes, 43.90 say there is an attack of bacterial disease and 19.51 say it is difficult in marketing.